Identification of FABP5 as an immunometabolic marker in human hepatocellular carcinoma. Issue 2 (1st July 2020) - Liu, Fangming; Liu, Weiren; Zhou, Shuang; Yang, Chunhui; Tian, Mengxin; Jia, Guangshuai; Wang, Han; Zhu, Bijun; Feng, Mingxiang; Lu, Yan; Qiao, Tiankui; Wang, Xinxin; et al.
Abstract : Background: Regulating T-cell metabolism is crucial for their anticancer activity. Therefore, understanding the function and metabolism of human tumor-infiltrating T cells is of broad interest and clinical importance. Methods: CD3 + CD45 + T cells were sorted from adjacent area or tumor core of human hepatocellular carcinoma (HCC), then the clusters and heterogeneity of T cells were further interrogated by single-cell transcriptomic profiling. 118 surgical samples from patients with HCC were histologically examined for infiltration of CD8 + T cells in tumor and adjacent tissue. Results: Single-cell transcriptomic profiling indicated that several exhausted T-cell (Tex) populations differentially coexisted in the tumor and adjacent tissue. CD137 identifies and enriches Tex with superior effector functions and proliferation capacity. Furthermore, enhanced fatty acid-binding protein 5 (FABP5) expression along with increased mitochondrial oxidative metabolism were evident in these CD137-enriched Tex. Inhibiting FABP5 expression and mitochondrial fatty acid oxidation impaired the anti-apoptosis and proliferation of CD137-enriched Tex. These observations have been verified by generating CD137 CART. Immunohistochemistry staining on the tissue microarray of 118 patients with HCC showed intra-tumoral FABP5 high CD8 + T-cell infiltration was linked to overall and recurrence-free survival. Conclusions: The tumor microenvironment can impose metabolic restrictions on T-cell function. CD137, a costimulatory molecule highly expressed on some Tex, uses exogenous fatty acids and oxidative metabolism to mediate antitumor immunity. The immunometabolic marker FABP5 should be investigated in larger, longitudinal studies to determine their potential as prognostic biomarkers for HCC.